Electrochromic smart window for modulation of infrared heat - Tan, Jun Hao (Nanyang Technological University, 2021)
Electrochromic (EC) smart windows have been on an arising attention in green building industry. The mechanism of this application enables the building to minimize the amount of heat, maintenance fees, glare from sunlight. These advantageous characteristics were derived from utilizing the convenience in modulating optical transmittance as well as infra-red (IR) irradiation with the use of small external voltage source. In the interest of an optimal EC properties for a EC smart window, a metal-doped tin oxide Inverse Opal (IO) Electrochromic Structures (ECs) with a deposited layer of amorphous tungsten oxide (SnO2-a-WO3) was fabricated in this novel work [1]. The layer of a-WO3 coated by electrodeposition (ECD) would further boost the EC efficiency [2]. Moreover, a rare-earth metal (i.e. neodymium (Nd)) will be introduced in this study aside from the transition metal oxides (TMO) (i.e.) molybdenum (Mo) and niobium (Nb), both would be employed as dopant materials in the IO nano-structure to elevate the EC behaviour. On top of co-doping investigation, the aim of the project will be upscaling the current sizing of the working samples to an effective conducting area of 10 x 10 cm2, along with the best optimal transmittance and EC performance.